O processo ensino-aprendizagem de história no ensino fundamental: seus limites, suas possibilidades - Calaça, Suelidia Maria (2008)
Study about the teaching-learning process in History, which intents to point limits and possibilities to this process, starting from its characterization and analysis and understanding of the concepts of history, time, society and culture, used by teachers and students. The field research was performed in the Municipal School of Basic Education Zumbi dos Palmares, located in the city of João Pessoa, Paraíba State, in the period between 1996 and 2006. To achieve the objective of the study, a number of research instruments were used, amongst which, interviews, questionnaires and exercises emphasizing conceptual learning. The theoretical-methodological premises of the qualitative research justify the use of these various instruments, and serve as base for the interpretation and analysis of the data. This study demonstrated that some limits and possibilities that are found in the teaching-learning process in History are originated in the school context of the 1st phase of basic education and remain in the 2nd phase of this education level, partly, because of the understanding that teachers and students have regarding the concepts of history, time, society and culture